Sport nutrition - Jeukendrup, A.; Gleeson, M. (Human Kinetics, 2025)
For students planning to work in a sport- or exercise-related career, it is crucial to understand the essential role nutrition plays in health, adaptations to physical activity and exercise, weight maintenance, and sports and exercise performance. Sport Nutrition, Fourth Edition With HK Propel Access, presents the principles and rationale for current nutrition guidelines for athletes and provides an in-depth look at the science behind sport nutrition.